Discovering Romans - Coffey, David (England : Crossway, 2000)
This introduction to the interpretation of Romans aims to encourage in-depth study of the text, and genuine grappling with the theological and historical questions raised, by providing a 'map' to the letter as a whole, and to key interpreters and interpretative debates. It will draw on a range of methodological approaches (author-, text- and reader-centred), as complementary rather than mutually exclusive ways of interpreting the text.In particular, this new introduction will attempt to reflect the growing scholarly attention to the reception history of biblical texts, increasingly viewed as a vital aspect of interpretation rather than an optional extra.
This introduction to the interpretation of Romans aims to encourage in-depth study of the text, and genuine grappling with the theological and historical questions raised, by providing a 'map' to the letter as a whole, and to key interpreters and interpretative debates.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc